MODEL PENYAMPAIAN AJARAN ISLAM BERBASIS MODERASI BERAGAMA DALAM PODCAST LOG IN DI CLOSE THE DOOR - Munirul Ikhwan; Amelia Dwi Septianingrum; Happy Susanto; Afiful Ikhwan (Universitas Muhammadiyah Ponorogo, 2022)
This research examines the delivery of Islamic teachings based on moderation in the